Clinical response to Nabiximols correlates with the downregulation of immune pathways in multiple sclerosis. (16th April 2018) - Sorosina, M.; Clarelli, F.; Ferrè, L.; Osiceanu, A. M.; Unal, N. T.; Mascia, E.; Martinelli, V.; Comi, G.; Benigni, F.; Esposito, F.; Martinelli Boneschi, F.
Abstract : Background and purpose: Nabiximols (Sativex ® ) is a cannabinoid‐based compound used for the treatment of moderate to severe spasticity in multiple sclerosis (MS). The aim of the study was to investigate the effect of the administration of Nabiximols on blood transcriptome profile of patients with MS and to interpret it in the context of pathways and networks. Methods: Whole‐genome expression profiling was performed in whole blood of 33 subjects with MS at baseline and after 4 weeks of drug treatment. Patients were classified as responders ( n = 19) and non‐responders ( n = 14). Pathway and network analyses on genes modulated by the drug were performed, followed by in vitro stimulation of peripheral blood mononuclear cells with pro‐inflammatory agents to support the immunomodulatory properties of the drug. Results: Individual effect size was modest; however, we observed a downregulation of several immune‐related pathways after 4 weeks of treatment, which was more pronounced when restricting analyses to responders. Interesting hub molecules functionally related to the immune system emerged from network analysis, including NFKB1, FYN, MAP14 and TP53 . The immunomodulatory properties of the drug were confirmed through in vitro assays in peripheral blood mononuclear cells collected from patients with MS. Conclusions: Our findings support the immunomodulatory activity of cannabinoids in patients with MS. Further studies in more specific cell types are needed to refine these results.